Uncovering the miRNA-mediated regulatory network involved in postharvest senescence of grape berries - Mingxin Feng; Ying Hu; Xin Yang; Jingwen Li; Haochen Wang; Yujia Liu; Haijun Ma; Kai Li; Jiayin Shang; Yulin Fang; Jiangfei Meng (Journal of Integrative Agriculture)
The postharvest senescence phase of table grapes comprises a series of biological processes. MicroRNAs (miRNAs) regulate downstream genes at the post-transcriptional level; however, whether miRNAs are involved in postharvest grape senescence remains unclear. We used small RNA sequencing to identify postharvest-related miRNAs in ‘Red Globe’ (Vitis vinifera) grapes harvested after 0, 30, and 60 d of storage at 4°C (RG0, RG30, RG60). In total, 42 known and 219 novel miRNA candidates were obtained. During fruit senescence, the expression of PC-3p-3343_1921, miR2950, miR395k, miR2111, miR159c, miR169q, PC-5p-1112_4500, and miR167b changed significantly (P<0.05). Degradation sequencing identified 218 targets associated with cell wall organization, tricarboxylic acid (TCA) cycling, pathogen defense, carbon metabolism, hormone signaling, the anthocyanin metabolism pathway, and energy regulation, of which ARF6, GRF3, TCP2, CP1, MYBA2, and WRKY72 were closely related to fruit senescence. We also verified that VIT_00s2146g00010, VIT_02s0012g01750, and VIT_03s0038g00160 with unknown functions are cleaved by senescence-related PC-5p-1112_4500 via the dual luciferase assay, and the transient transformation of grape berries showed that they regulate berry senescence. These results deepen our understanding of the role of miRNAs in regulating grape berry senescence and prolonging the shelf life of horticultural products. Based on these results, we propose a new theoretical strategy for delaying the postharvest senescence of horticultural products by regulating the expression of key miRNAs (e.g., PC-5p-1112_4500), thereby extending their shelf life.